PENGARUH EKSTRAK SALVIA SPLENDENS SELLO TERHADAP PERTUMBUHAN JAMUR ALTERNARIA SOLANI (ELL.& MART.) JONES & GROUT DAN BAKTERI PSEUDOMONAS SOLANACEARUM E.F. SMITH SERTA PENGARUHNYA TERHADAP TANAMAN TOMAT, LYCOPERSICON LYCOPERSICUM (L.) KARSTEN - , Salni
Abstrack A research on the effects of the extracts of Salvia splendens on the growth of Alternaria solani and Pseudomonas solanacearum and their effects on tomato (Lycopersicon lycopersicum) has been conducted. The experimental design used was Complex Random Design (CRD) with six treatments and five replications. The preliminary experiment to know the activity of the S. splendens extracts on the growth of A. solani and P. solanacearum the ethanol extract, n-hexane and dichloromethane fractions were used. It was found that dichloromethane fraction was active against A. solani and ethanol extract was active against P. solanacearum. The dichloromethane fraction with the concentrations of 0.00, 0.40, 0.80, 1.20, 1.60 and 2.00 percent (w/v) were tested on the growth of A. solani in vitro, the seed germination and growth of the radical of tomato seedling. The ethanol extract with the concentrations of 0.00, 0.50, 1.00, 1.50, 2.00 and 2.50 percent (w/v) were also tested on the growth of P. solanacearum in vitro, the seed germination and growth of the radical of tomato seedling. Dichloromethane fraction with the concentrations of 0.00 and 1.20 percent and ethanol extract with the concentrations of 0.00 and 1.00 percent were tested on the vegetative growth of tomato plant. The result showed that the dichloromethane fraction inhibited the growth of A. solani at MIC value of 1.20 percent (MIC = Minimum Inhibitory Concentrations) during five x 24 hours observation and inhibited the germination and the growth of the radical of tomato seedling, but did not inhibit the vegetative growth of tomato plant. The ethanol extract inhibited the growth of P. solanacearum at MIC value of 1.00 percent during 24 hours and inhibited the germination and the growth of the radical of tomato seedling, but did not inhibit the vegetative growth of tomato plant.